The Influence of Symbols and Equations on Understanding Mathematical Equivalence. (May 2015) - Powell, Sarah R.
Students with mathematics difficulty demonstrate lower mathematics performance than typical-performing peers. One contributing factor to lower mathematics performance may be misunderstanding of mathematics symbols. In several studies related to the equal sign (=), students who received explicit instruction on the relational definition (i.e., "the same as") of the equal sign demonstrated improved performance on equation solving and equal-sign understanding. In one study, equal-sign instruction improved performance on word problems when students used an equation to set up and solve word problems. Implications for teachers include (a) providing explicit instruction on a relational definition of the equal sign and (b) providing more exposure to equation types (e.g., 9 – 5 = _ + 3) students rarely see in mathematics textbooks.